Anthony J. Langlois, Sexuality and Gender Diversity Rights in Southeast Asia. - Maity, Abhijit (SARE: Southeast Asian Review of English, 2023)
In Sexuality and Gender Diversity Rights in Southeast Asia, Anthony J. Langlois offers new perspectives on the nature of implementation of laws, the necessity of rights claiming and the prevalence of violence and discrimination around the lives of LGBTIQ+ people. This book is a call for new public policy and social norms to be (re)formed in Southeast Asian regions for those who are sexually non-conforming, and hence, are treated as second (read lower) class citizens. On the face of rapid socio-political changes and multiple preventive measures taken by the international human rights regime, the book argues that “most Southeast Asian states do not recognise the need for such rights” (1). However, in response to such incapacitated geo-political frameworks, this book considers many civil organisations and their political participation in rights claiming for the “people of diverse sexual orientation, gender identity expression and sex characteristics (SOGIESC)”. This book also attempts to connect the Southeast Asian LGBTIQ+ rights claiming movements to a larger international human rights regime.